2010
DOI: 10.1089/ten.tec.2009.0247
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial Function Determines the Viability and Osteogenic Potency of Human Mesenchymal Stem Cells

Abstract: Advanced therapies medicinal products (ATMPs) have introduced innovative cell-based products. However, the regulatory demands for characterization of ATMPs are currently unable to adequately address the safety of such products. As recent studies have emphasized the role of mitochondria in the osteogenic differentiation of human mesenchymal stem cells (hMSCs), we have studied in detail the viability and osteogenic differentiation potency of the hMSCs intended for use as ATMPs based on analyses of the mitochondr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
36
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(38 citation statements)
references
References 34 publications
2
36
0
Order By: Relevance
“…The Dwm is related to apoptosis due to the fact that dissipation of Dwm is a critical event in apoptosis process [11]. It is convincing that the high Dwm cell population possesses a stronger resistance to apoptotic inducers than low Dwm cell population in cultured hMSCs (human mesenchymal stem cells) [32]. The stronger apoptotic resistance of CSCs compared to the non-CSCs in human oral squamous cell carcinoma cell line Ho-1-N-1 was also related to Dwm [33].…”
Section: Mitochondria Membrane Potential (Dwm) In Cscsmentioning
confidence: 99%
“…The Dwm is related to apoptosis due to the fact that dissipation of Dwm is a critical event in apoptosis process [11]. It is convincing that the high Dwm cell population possesses a stronger resistance to apoptotic inducers than low Dwm cell population in cultured hMSCs (human mesenchymal stem cells) [32]. The stronger apoptotic resistance of CSCs compared to the non-CSCs in human oral squamous cell carcinoma cell line Ho-1-N-1 was also related to Dwm [33].…”
Section: Mitochondria Membrane Potential (Dwm) In Cscsmentioning
confidence: 99%
“…It is thought that mitochondrial function and integrity may affect SC viability, the proliferative and differentiation potential of these cells, and their lifespan [111]. Heerdt et al found that the mitochondrial membrane potential (Dcm) is associated with a cell's tumorigenicity.…”
Section: Mitochondrial Membrane Potentialmentioning
confidence: 99%
“…Mitochondrial inner membrane potential (DC m ) specific dye 5,5',6,6'-tetrachloro-1,1',3,3'-tetraethylbenzimidazolcarbocyanine iodide ( JC-1; Sigma-Aldrich) was used as earlier described [30]. Cells were suspended in PBS and incubated with 1 mM JC-1 for 20 min at room temperature.…”
Section: Flow Cytometric Detection Of Mitochondrial Inner Membrane Pomentioning
confidence: 99%
“…Recently, more attention has been focused on mitochondria and cellular bioenergetics of stem cells, which has revealed their unique metabolic status [27][28][29]. It has been shown that mitochondrial activity or dormancy plays a major role in maintaining the undifferentiated state, whereas the proper activation and function of mitochondria is essential during the differentiation processes [29][30][31]. In addition, mitochondrial reactive oxygen species (ROS) regulate the differentiation of several stem cell types; and recently, ROS have been shown to inhibit adhesion of hMSCs to the site of injury [32][33][34].…”
Section: Introductionmentioning
confidence: 99%